The Role of Digital Marketing in Enhancing the Attractiveness of Tourism Destinations on New Year's Eve - Muhammad Ade Kurnia Harahap; Hisnol Jamali; Ahmad Yani (Jurnal Minfo Polgan, 2023)
New Year's Eve is considered a global celebration and a significant attraction for tourists. In the continually evolving digital era, digital marketing has become a crucial instrument in promoting tourism destinations. The purpose of this research is to analyze the role of digital marketing in increasing the allure of tourism destinations on New Year's Eve. The study employed a comprehensive literature review utilizing qualitative analysis to gain a thorough understanding of the topic spanning from 2002 to 2023. The findings indicate that, in enhancing the appeal of tourism destinations on New Year's Eve, the role of digital marketing is paramount. Through creativity in content, leveraging VR and AR technologies, and facilitating online booking convenience, tourism destinations can capture the attention of tourists and ensure an unforgettable New Year's experience. Collaboration with digital influencers also proves to be an effective strategy in generating positive online buzz.